DIGITAL NATIVE: A STUDY ON THE FIRST-YEAR STUDENT - Nur Rakhmawati, Deny Efita; Kusuma, Agung Wiranata (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
The digital native generation emergent triggers the educational practitioner to develop a new way of approaching the teaching practice in the classroom. As it is claimed that this generation has a unique characteristics and way of learning. Therefore, this paper explore the experience of the first year student of English language and letters department in using technology. Students were asked about their access to, use of and preferences for a wide range of established and emerging technologies and technology based tools using a questioner developed to assess their level of digital nativity. The results show that many first year students are highly tech-savvy. However, each student’s experience on the use of technologies and tools (e.g. computers, mobile phones) show considerable variation. The findings are analyzed using the Prensky’s theory on the ‘Digital Natives’ and the implications for using technology to support teaching and learning in higher education. The reported data indicate that for a range of emerging technologies were used intensively by the students. Furthermore, the majority of the respondents also claimed that they used the tools and technology to support their study. However, it is inconclusive as how the student integrate the tools and technology in their study.